Dynamic Changes in Rumen Microbial Diversity and Community Composition Within Rumen Fluid in Response to Various Storage Temperatures and Preservation Times - Chang Liu; Jin Cheng; Yunong Xie; Kehui Ouyang; Mingren Qu; Ke Pan; Qinghua Qiu (Veterinary Sciences)
The aim of this study was to investigate the effects of storage temperature and preservation time on the microbial diversity and community composition of rumen fluid. Rumen fluid samples were collected from six Hu sheep fed on a high-forage diet and stored at −80 °C and −20 °C for intervals of 0, 7, 14, 30, 60, 120, and 240 days. DNA was extracted at each time point for 16S rRNA gene sequencing to evaluate the rumen microbial diversity and community composition. The results showed that storage temperature affected only the relative abundance of Proteobacteria, with no substantial impact on alpha-diversity or other microbial groups (p > 0.05), and no significant interaction effects were observed between storage temperature and preservation time (p > 0.05). Alpha-diversity indices such as Chao1, observed species, and PD whole tree showed dynamic changes after 7 days of storage, while the relative abundances of Verrucomicrobiota and Christensenellaceae R-7 group, as well as the energy metabolism metabolic pathway, exhibited significant alterations after 14 days of storage (p < 0.05). Notably, Patescibacteria, Rikenellaceae RC9 gut group, and Veillonellaceae UCG-001 abundances demonstrated significant changes after 240 days of storage (p < 0.05). Both principal coordinates analysis (PCoA) and non-metric multidimensional scaling (NMDS) showed distinct overlaps. This study suggests that storing rumen fluid at −80 °C and −20 °C does not influence rumen microbial diversity and community composition, whereas the storage time significantly impacts these factors, with most differences emerging after 14 days of preservation. Consequently, it is advised that the analysis of microbial diversity and community composition in rumen fluid samples be conducted within 14 days post-collection.